PENERAPAN PENDEKATAN CULTURALLY RESPONSIVE TEACHING (CRT) MELALUI GAME WORDWALL UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA KELAS V SDN SARIREJO - Kayniya, Marshanda Shawma; Purnamasari , Veryliana; Nurhayati, Ri’ah (Trihayu: Jurnal Pendidikan Ke-SD-an, 2025)
This research aims to determine the application of the Culturally Responsive Teaching (CRT) approach through Worwall media to improve grade 5 mathematics learning outcomes. This type of research is Classroom Action Research (PTK) which is carried out in two cycles. The subjects of this research were 25 VA class students at SDN Sarirejo Semarang. Data collection techniques in this research are observation, tests, evaluation and documentation. The test technique uses pretest and posttest while the non-test technique uses observation, questionnaires and documentation. Data analysis techniques using quantitative descriptive.  The results of the research show that the application of the Culturally Responsive Teaching (CRT) approach through wordwall media has improved student learning outcomes. The research results showed that in the pre-cycle, the average learning completeness was only 20%. After cycle 1, student learning outcomes increased by 50% to 70%. Until the second cycle, students who had completed increased to 90% and those who had not completed 10%. The conclusion of this research is that the application of Culturally Responsive Teaching (CRT) through Wordwall media is effective for improving student learning outcomes.